2022
DOI: 10.5114/ada.2022.113612
|View full text |Cite
|
Sign up to set email alerts
|

Increased serum levels of interleukin-17 in patients with alopecia areata and non-segmental vitiligo

Abstract: Introduction: Alopecia areata (AA) and vitiligo are both skin diseases of autoimmune origin. AA is characterized by patchy hair loss primarily on the scalp but may involve other areas as well, while vitiligo is caused by the destruction of melanocytes and results in the appearance of white patches on any part of the body. Many facts indicate similar pathogenesis of these diseases. Both dermatoses are associated with frequent coexistence of other autoimmune diseases and share common genetic risk factors. Recent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…IL-17, a Th17 cytokine, mediates signaling through an NF-κB activator 1–dependent pathway that is independent of Jak signaling ( Gaffen, 2009 ). Serum levels of IL-17 were elevated in patients with vitiligo compared with those in healthy controls ( Karagün and Baysak, 2020 ; Tomaszewska et al., 2022 ) and were also positively correlated with disease duration, activity, and extent ( Czarnowicki et al., 2019 ; Sushama et al., 2019 ). Importantly, IL-17RA was upregulated in group 2 relative to that in group 1, indicating that baseline serum IL-17 levels may also have an inverse relationship with achieving clinical response.…”
Section: Discussionmentioning
confidence: 98%
“…IL-17, a Th17 cytokine, mediates signaling through an NF-κB activator 1–dependent pathway that is independent of Jak signaling ( Gaffen, 2009 ). Serum levels of IL-17 were elevated in patients with vitiligo compared with those in healthy controls ( Karagün and Baysak, 2020 ; Tomaszewska et al., 2022 ) and were also positively correlated with disease duration, activity, and extent ( Czarnowicki et al., 2019 ; Sushama et al., 2019 ). Importantly, IL-17RA was upregulated in group 2 relative to that in group 1, indicating that baseline serum IL-17 levels may also have an inverse relationship with achieving clinical response.…”
Section: Discussionmentioning
confidence: 98%
“…A developmental relationship between Th1 and Th17 cells, with Th1-induced IFNγ actually promoting the Th17 pathway, has been suggested [ 86 , 87 ]. There has been some indication of IL-17 activation in a CD8+ driven mouse model of AA [ 30 ], and increased serum levels of IL-17 have been found in a number of studies in AA patients when compared to controls [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 31 , 32 , 33 ]. Although the Th17 pathway has continued to be implicated in AA, a genetic underpinning for this has not been established and the potential familial dysregulation of the Th17 pathway in keeping with the autoimmune diathesis seen in families of AA patients has not been assessed to date.…”
Section: Discussionmentioning
confidence: 99%
“…Th17 cells have been shown to be relevant in several autoimmune diseases including inflammatory bowel disease, multiple sclerosis, psoriasis, eczema, rheumatoid arthritis, Sjögren’s syndrome, and vitiligo [ 13 , 14 , 15 ]. Specifically in AA, several studies on the role of Th17 cells in AA have shown increased serum levels of IL-17 in AA patients when compared to controls [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ] ( Table 1 ), and skewing towards the Th17 pathway [ 19 , 29 ]. These findings are supported by studies indicating IL-17 activation in a murine model of alopecia [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, studies have reported that patients with alopecia areata don't show significant improvement with anti-IL-17 therapy secukinumab. Therefore, the contribution of Th17/IL-17 in the pathogenesis of alopecia areata is still controversial [23] .…”
Section: Alopecia Areata (Aa)mentioning
confidence: 99%